Formulasi Kukis Berbahan Tepung Labu Kuning (Cucurbita moschata Duch) dan Tepung Terigu Dengan Penambahan Pisang Ambon (Musa paradisiaca) - Marintan Paskalia Manurung; Seveline Seveline; Moh Taufik (JURNAL AGROINDUSTRI HALAL, 2021)
Cookies is one type of biscuit which is processed from soft dough, has high levels of fat and sugar, relatively crunchy and when broken, the cross section is less dense textured. One alternative ingredient that can be used in making cookies is pumpkin flour. This research aims to formulate cookies made from pumpkin flour and wheat flour with addition of ambon banana. The use of ambon banana in making cookies is to replace eggs for people who have vegetarian lifestyle. The results showed that the yield in making pumpkin flour was 10.59% and pumpkin flour had a moisture content of 5.65%, ash content of 1.42%, protein content of 6.50%, fat content of 0.50%, carbohydrate content of 86.21%. The organoleptic test indicated that F1 cookies (15% pumpkin flour substitution and 20% banana ambon addition) and F2 cookies (15% pumpkin flour substitution and 30% banana ambon addition) have the same level of preference as control cookies.